Percepção de alunos de graduação acerca de como a educação ambiental vem sendo trabalhada na universidade federal rural do semi-árido - Lima, Flávia Giglianne Freitas (Universidade Federal Rural do Semi-Árido, 2019)
Environmental Education has the purpose of promoting changes in the values, attitudes, habits and behaviors of citizens through the balance between man and the environment. Following this bias, Higher Education Institutions are increasingly concerned and engaged in incorporating this education into their academic activities. Incorporating models of teaching and learning increasingly focused on solving environmental problems, institutions are reorganizing their education, research and extension activities towards sustainability. Therefore, it is interesting to evaluate if this theme has been worked on in institutions, if it is noticeable by the students and to examine their relations in the construction of values, attitudes and behaviors that are environmentally responsible. Thus, the objective of this research is to examine the relationships between the perception of the insertion of Environmental Education and the attitudes, values and behaviors environmentally responsible of students of undergraduate courses at UFERSA. By adapting the study by Silva (2014), in which the field research was conducted, the data were obtained through electronic questionnaires that were sent through the Integrated Academic Activity Management System. Data analysis was performed using descriptive statistics and exploratory factor analysis. In the descriptive analysis of the results obtained, in which the first analyzed construct was the ecological behavior, it presented two positive dimensions: water and energy saving and urban cleaning. In the second construct of ecological values, the three biospheric, altruistic, and selfish dimensions were statistically positive. In the construction of ecological attitudes, the anthropocentric attitudes dimension was the most significant among them. The descriptive analysis of the perception scale of the insertion of Environmental Education reveals that students perceive the measures implemented on campus. In the exploratory factor analysis Environmental Education had a statistically significant correlation with construct ecological behavior, the dimensions water and energy economy, urban cleanliness and consumerism activism presented the strongest correlation. In the construct of values the three biospheric, altruistic and selfish dimensions correlated significantly with all dimensions of perception of Environmental Education and in the construct of attitudes the anthropocentric and acocentric dimensions showed significant correlation.
Keywords: Percepção ambiental.; Valores ambientais; Atitudes ambientais; Comportamento ambiental; Environmental perception; Environmental values; Environmental attitudes; Environmental behavior; MULTIDISCIPLINAR::CIENCIAS AMBIENTAIS::AMBIENTE, TECNOLOGIA E SOCIEDADE